Bedrock and detrital zircon thermochronology to unravel exhumation histories of accreted tectonic blocks: An example from the Western Colombian Andes. (November 2020) - Zapata, S.; Patiño, A.; Cardona, A.; Parra, M.; Valencia, V.; Reiners, P.; Oboh-Ikuenobe, F.; Genezini, F.
Abstract: The Northern Andes are the result of multiple tectonic phases, which include extensional and compressional volcanic arcs, strike-slip fragmentation, and accretion of exotic terranes. The alternations of these tectonic settings have overprinted and fragmented the geological record, which has hindered precise paleogeographic and tectonic reconstructions. In the western segment of the Colombian Andes, the oceanic-cored Western Cordillera (WC) and the continental Central Cordillera (CC) are separated by the Romeral Fault Zone (RFZ). This segment of the Andes preserves the record of Cretaceous back-arc extension, the onset of compression, and the accretion of the Caribbean plateau during the Late Cretaceous-Paleocene. To refine the tectonic evolution of the Western Colombian Andes, this study documents new detrital zircon fission-track (ZFT) data from the Meso-Cenozoic sedimentary cover in the CC, the RFZ, and the WC; new ZFT and zircon helium (ZHe) bedrock data from the CC and the RFZ; and new U–Pb detrital data from the Miocene sedimentary cover of the RFZ. Within the RFZ, we obtained bedrock ZFT ages of 239.0 ± 11.0 Ma and 111.1 ± 4.3 Ma, and detrital ZFT data from the Abejorral Formation are interpreted as the result of post-magmatic cooling and Cretaceous rifting. Late Cretaceous to Eocene ZFT and ZHe ages ( 61–50 Ma) in the CC and detrital ZFT data in the WC record exhumation and deformation of the CC during and after the collision of the Caribbean plateau with the continental margin. Finally, detrital U–Pb and ZFT data from the Amagá Formation record the formation of a Miocene intermountain basin. This study reconstructs the basin geometries and the deformation patterns before, during, and after the collision of the Caribbean plateau with the South American margin. We highlight that in accretionary orogens, in which prolonged deformation and erosion have removed the sedimentary cover, the quantification of differential basement exhumation is key to reconstruct thick-skin deformation and to define major tectonic boundaries. Highlights: The collision between the South American margin and the Caribbean plateau. Detrital and bedrock zircon thermochronology to constrain thick-skin deformation. The importance of vertical exhumation to understand major tectonic boundaries.